Participation with online recovery specific groups - findings from the UK Life in Recovery survey 2015. Issue 4 (2nd October 2018) - Graham, Simon; Irving, Jamie; Cano, Ivan; Edwards, Michael
ABSTRACT: As the concept of recovery has expanded, and become embedded in drug and alcohol policy, so too has the proliferation of online recovery support. This article explores data from the UK Life in Recovery survey, focusing on online recovery methods categorized as online groups, websites, and smartphone applications. Although 301 people (39.30%) reported involvement with at least one online recovery method, chi-squared tests reveal significant associations between people in stable recovery (5 years or more) and the use of recovery applications (Cramer's V  = .114), as well as between people in full-time employment and the use of online recovery websites or recovery applications. Having dependent children was not associated with use of any online recovery method, yet gender was (Cramer's V  = .088). This study extends the relatively limited literature and knowledge base of online recovery methods. Although the evidence points to higher engagement of recovery websites and apps for people in stable recovery, encouraging online recovery methods for individuals in early recovery may support recovery efforts when the risk of returning to substance misuse and active using social networks remains high. Further research should investigate the mechanisms of recovery change, with a focus on gender differences.